Development of Passive Quarter Car Suspension Prototype - Che Amran, Aliza; Fen, Ying Chin; Md Ghazaly, Mariam; Chong, Shin Horng (2014)
In this paper, a construction of a prototype to represent passive vehicle suspension system for quarter car model is considered. The prototype is represented by two degree-of freedom quarter-car model which are conventionally used by researchers. This laboratory equipment is developed in order to familiarize students with 2 DoF passive suspension system model. It consists of two masses, two springs and a damper. This equipment is easily dismantled and could be assembled with different spring and damper constants which contribute to different characteristics of the suspension system. A number of experiments have been carried out using the experiment setup in order to identify the suspension system characteristics i.e. experiments with different vehicle body mass, different period for one pulse and different pulse width of input pressure of the road excitation have been conducted. The experiment results are evaluated based on the vehicle body displacement and tire displacement of the prototype. Experiment results show that the pulse width of the input pressure or road profile is directly affected the characteristic of this passive suspension system. Lastly, simulations were done in order to compare the simulation and experiment results. Next step is to implement active control to this system via active actuators.